ASSOCIATION OF RELIGIOUS ORIENTATION WITH DEPRESSION, ANXIETY AND STRESS AMONG MALE PATIENTS WITH SUBSTANCE USE DISORDER IN PAKISTAN - Khan, Muhammad Ali; Shahzad, Salman; Bano, Nasreen; Siddiqui, Mehreen; Ali, Ahmad (Journal of Pakistan Psychiatric Society, 2024)
OBJECTIVES Religion has been discussed in numerous research studies with reference to its significance in mental health outcomes. It has gained its attention of researchers due to its pivotal role in the lives of human kind. Present study aims to investigate the predictive relationship of religious orientation on psychological constructs including depression, anxiety & stress) in male patients with substance use disorder (SUD). STUDY DESIGN This study was conducted by using a Cross-sectional study design. PLACE AND DURATION OF STUDY Study was carried out from April- July, 2018 in Karachi Pakistan. PARTICIPANTS AND METHODS The sample included 200 Muslim male patients with SUD. The age ranges between 18 to 45 years (M =28.14; SD =6.55) were taken from substance use treatment and rehabilitation centers located in Karachi, Pakistan using purposive sampling. Personal Information Form and Urdu translations of the scales including Muslim Attitude towards Religion Scale (MARS) and Depression Anxiety and Stress Scale (DASS-21) were used to conduct this study. RESULTS Results revealed a significant association of religious orientation with the variables of psychological distress, i.e., depression (adj R2=.994, F (4, 196) =5424.24, P < .01(, anxiety (adj R2=.97, F (4,196) =1309.5, P < .01(, and stress (adj R2 =.991, F (4,196) =3854.2, .00 P < .01(. CONCLUSION Religion has significant role in wellbeing of its believers in general, and specifically among patients with SUD. Present findings also show that religious orientation has significant contribution in psychological distress such as, “depression”, “anxiety” and “stress” in male patients with SUD. Substance use treatment practitioners may develop interventions by considering the cultural and religion aspect for better treatment outcome and to improve their wellbeing. Further, religious orientation may serve an important variable to have better treatment outcome, and to address mental health issues which may also improve their wellbeing.